International Standards and Accounting Education (2013)
From the 90´s, proposals aimed at the preparation of standards which guide the Public Accounting, have been formulated from international agencies and global trade entities associated with this profession. Although these proposals, particularly promoted by International Federation of Accountants (IFAC) have been controversial, their incorporation into the accountants training has been done gradually through internal legislation.The comparison of known proposals reveals their background, which is to shape some contours of the education and accounting profession in accordance to homogenizing claims of financial globalization, from which an accountant with a reductionist and instrumental vision would result, as a carrier of competences geared towards market demands.